Fabrication of novel hybrid Z-Scheme WO3@g-C3N4@MWCNT nanostructure for photocatalytic degradation of tetracycline and the evaluation of antimicrobial activity. (January 2022) - Manikandan, V.S.; Harish, S.; Archana, J.; Navaneethan, M.
Abstract: Exploring highly efficient visible-light-driven photocatalyst for the elimination organic pollutants is a great concern for constructing sustainable green energy systems. In the current work, a novel hybrid ternary WO3 @g-C3 N4 @MWCNT nanocomposites have been fabricated for visible-light-driven photocatalyst by self-assembly method. The as-prepared photocatalyst was examined by XRD, Raman, FESEM, HRTEM, XPS EDS, EIS, UV–visible DRS, and PL analysis. The experimental results revealed that the photocatalytic activity of WO3 @g-C3 N4 @MWCNT nanocomposites on the degradation of Tetracycline (TC) is 79.54% at 120 min, which is higher than the binary WO3 @g-C3 N4 composite and pristine WO3 . The improved degradation performance towards TC is recognized for its higher surface area, intense light absorption towards the visible region, and enhanced charge separation efficiency. Consequently, the fabricated catalyst endows a promising application for antibiotic degradation. Graphical abstract: Image 1 Highlights: We fabricated WO3 /g-C3 N4 /MWCNT hybrid nanostructure by simple low temperature hydrothermal process. Photocatalytic degradation of TC were observed under visible light. WO3 /g-C3 N4 /MWCNT sample showed excellent degradation of tetracycline. WO3 /g-C3 N4 /MWCNT hybrid structure has been probed as a potential applicant for visible light driven photocatalyst.